OM UDVIKLINGSPSYKOLOGIEN - EN PERSONLIG BERETNING. - Bernth, Inger (Psyke & Logos, 2022)
A review of developmental psychology in Copenhagen from 1894 to year 2000. With a brief reference to international trend examples from the literature and personal experiences illustrate how psychology of childhood and adolescence was turned into developmental psychology. Also how the orientation for more than 50 years was educational while medical doctors were responsible for the clinical aspects. A biologicalpsychological- cultural approach where the child is not hidden by the shadow of theory is recommended.